2003
DOI: 10.1046/j.1464-5491.2003.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Development, reliability and validity of the Diabetes Illness Representations Questionnaire: four studies with adolescents

Abstract: The data reported here suggest that the DIRQ has the potential to be a useful tool for clinical assessment and evaluating the impact of psycho-educational and medical interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 17 publications
3
47
0
4
Order By: Relevance
“…Most studies report that patients who believe their condition is more controllable have better self-care in the areas of diet, exercise and glucose testing (Glasgow, Hampson, Strycker, & Ruggiero, 1997;Griva et al, 2000;Hampson, Glasgow, & Foster, 1995;Hampson, Glasgow, & Toobert, 1990;Skinner & Hampson, 1998;Skinner & Hampson, 2001;Skinner, Hampson, & Fife-Schaw, 2002;Skinner et al, 2003;Skinner, John, & Hampson, 2000). Fewer studies have reported associations between illness perceptions and medication self-care (Griva et al, 2000;Skinner et al, 2002).…”
Section: Illness Perceptions and Self-carementioning
confidence: 95%
“…Most studies report that patients who believe their condition is more controllable have better self-care in the areas of diet, exercise and glucose testing (Glasgow, Hampson, Strycker, & Ruggiero, 1997;Griva et al, 2000;Hampson, Glasgow, & Foster, 1995;Hampson, Glasgow, & Toobert, 1990;Skinner & Hampson, 1998;Skinner & Hampson, 2001;Skinner, Hampson, & Fife-Schaw, 2002;Skinner et al, 2003;Skinner, John, & Hampson, 2000). Fewer studies have reported associations between illness perceptions and medication self-care (Griva et al, 2000;Skinner et al, 2002).…”
Section: Illness Perceptions and Self-carementioning
confidence: 95%
“…Yet, there is very little research examining the stability or change in illness perceptions in patients with cardiac problems [23]. Moreover, no study has examined longitudinal changes following successful surgical treatment, such as valve replacement.…”
Section: Illness Perceptions In Cardiac Diseasesmentioning
confidence: 97%
“…Perceptions of health threat were assessed using two scales measuring perceived seriousness of and vulnerability for diabetes, after recent studies showing that perceptions of seriousness do not necessarily translate into feelings of personal vulnerability (7,16). The perceived seriousness scale was based on the diabetes illness representations questionnaire (17) and used three items to explore patients' beliefs about the seriousness of diabetes in general. Patients were asked whether they agreed with each statements on a 5-point scale, ranging from strongly disagree to strongly agree, with a score of 3 as neutral.…”
Section: Methodsmentioning
confidence: 99%